Q&A - Ask Doubts and Get Answers

Sort by :
Clear All
Q
Engineering
135 Views   |

If the sum of the first ten terms of the series

then m is equal to:

• Option 1)

102

• Option 2)

101

• Option 3)

100

• Option 4)

99

As we learnt in

Summation of series of natural numbers -

$\sum_{k=1}^{n}K^{2}= \frac{1}{6}n\left ( n+1 \right )\left ( 2n+1 \right )$

- wherein

Sum of  squares of first n natural numbers

$1^{2}+2^{2}+3^{2}+4^{2}+------+n^{2}= \frac{n(n+1)\left ( 2n+1 \right )}{6}$

$\left ( 1\frac{3}{5} \right )^{2}+\left ( 2\frac{2}{5} \right )^{2}+\left ( 3\frac{3}{5} \right )^{2}+4^{2}+\left (4\frac{4}{5} \right )^{2}----is \frac{16}{5}n$

$\Rightarrow \left ( \frac{8}{5} \right )^{2}+\left ( \frac{12}{5} \right )^{2}+\left ( \frac{16}{5} \right )^{2}+\left ( \frac{20}{5} \right )^{2}+ -----$

$\therefore\frac{1}{25} \left [ 8^{2}+12^{2}+16^{2}+20^{2}+ --- \right ]$

$\therefore\frac{1}{25}\times4^{}2 \left [ 2^{2}+3^{2}+4^{2}+5^{2}+--- \right ]$

$=\frac{16}{25} \left [ 1^{2}+2^{2}+3^{}2+-----11^{2}-1\right ]$

$\Rightarrow \frac{16}{25}\left [ \frac{11\times12\times23}{6}-1 \right ]=\frac{16}{5}n$

$\therefore 11\times46-1=5n$

$506-1=5n$

$505=5n$

$\therefore n=101$

Option 1)

102

Incorrect option

Option 2)

101

Correct option

Option 3)

100

Incorrect option

Option 4)

99

Incorrect option

View More
Engineering
199 Views   |

If the 2nd, 5th and 9th terms of a non-constant A.P. are in G.P., then the common ratio of this G.P. is :

• Option 1)

• Option 2)

• Option 3)

• Option 4)

As we learnt in

Common ratio of a GP (r) -

The ratio of two consecutive terms of a GP

- wherein

eg: in 2, 4, 8, 16, - - - - - - -

r = 2

and in 100, 10, 1, 1/10 - - - - - - -

r = 1/10

${A}, {B},{C}$ are in  G.P where ${A}, {B},{C}$  are Terms of an A.P

Let first term is a and common difference is d, and common ratio be r then

A = a+d

B = a+4d

C= a+8d

$\therefore \: \frac{B}{A}=\frac{C}{B}=\frac{r}{1}$

$\frac{a+4d}{a+d} =\frac{a+8d}{a+4d}=\frac{r}{1}$

$\therefore \frac{a+4d+a+d}{a+4d-a-d}=\frac{r+1}{r-1}$

$\Rightarrow \frac{2a+5d}{3d}=\frac{r+1}{r-1}-----(i)$

$\frac{a+8d+a+4d}{a+8d-a-4d} =\frac{r+1}{r-1}$

$\Rightarrow \frac{2a+12d}{4d}=\frac{r+1}{r-1}------(ii)$

from (i) and (ii)

$\frac{2a+5d}{2a+12d}=\frac{3}{4}$

$8a+20d=6a+36d$

2a=16d

a=8d

$\Rightarrow \frac{r+1}{r-1}=\frac{2\times8d+5d}{3d}$$=\frac{16d+5d}{3d}$$=\frac{21}{3}=7$

$\therefore r+1=7r-7$

$8=6r$

$r=\frac{4}{3}$

Option 1)

Incorrect option

Option 2)

Correct option

Option 3)

Incorrect option

Option 4)

Incorrect option

View More
Exams
Articles
Questions